The Determinants and Effects of Clients Following Audit Partners Who Switch Audit Firms. Issue 3 (27th May 2019) - Chang, Wen-Ching; Choy, Hiu Lam; Lin, Huey-Yeh; Koo, Meihua
Abstract: We examine the determinants of clients' decision to follow departing partners to new audit firms and the effect of this decision on the likelihood of financial restatements. Using Taiwanese audit partner turnover data from 1984 to 2010, we find that clients are more likely to follow departing partners when the partners have more clients, longer tenure, and when both lead and concurring partners leave simultaneously. By contrast, clients are more likely to stay with their incumbent audit firms when the firms are one of the Big Four or when only the concurring partners leave. The extended partner tenure due to clients following departing partners, however, does not enhance audit quality. In fact, clients that stay at the incumbent firm experience a significant decrease in the probability of financial restatements in the first year after the audit partners leave, but clients that follow do not.